The Impact of Financial Literacy and Digital Finance Applications on Household Consumption Patterns in the Digital Age: Evidence from Makassar - Sri Prilmayanti Awaluddin; Andi Ummul Khair; Eka Wijaya Paula; Faisal Rizal Zainal; Deni Anggreani Sutomo (Jurnal Informasi dan Teknologi, 2025)
This study aims to examine the influence of financial literacy and digital financial applications on household consumption patterns in the digital era, with a case study conducted in Tamalanrea District, Makassar City. The research uses a quantitative associative approach with a multiple linear regression method. Data were collected from 100 household respondents selected through purposive sampling, based on their active use of digital financial services such as e-wallets, mobile banking, and paylater features. The primary variables studied include financial literacy (X₁), digital financial application usage (X₂), and household consumption patterns (Y). The results show that both financial literacy and digital financial application usage significantly affect household consumption patterns, both partially and simultaneously. Financial literacy positively influences rational financial behavior, including budgeting, prioritizing needs over wants, and managing spending. Meanwhile, the use of digital financial applications also positively affects consumption patterns by increasing access and ease of transactions, although it may also trigger impulsive behavior when not controlled by financial awareness. The F-test result shows that the model is statistically significant, with an R² value of 0.627, indicating that 62.7% of the variation in household consumption patterns can be explained by the two independent variables. This study highlights the importance of strengthening digital financial literacy and developing public policies to regulate fintech platforms. Efforts should be directed at building a healthy consumption ecosystem in the digital economy through collaborative efforts between the government, education institutions, and financial technology providers.